A Novel and Simple Process for Nanosized Mg‐Mn Ferrite Preparation from Solution Combustion Method and Study of its Characteristics. Issue 6 (30th April 2013) - Lwin, Nilar; Mohd Noor, Ahmad Fauzi; Sreekantan, Srimala; Othman, Radzali; Thant, Aye Aye
<x xml:space="preserve">Abstract</x> A novel solution combustion method has been used to prepare Mg‐Mn ferrites of various compositions, Mg0.9Mn0.1Fe1‐xO4 where x = 0.2, 0.4, 0.6, 0.8, and the properties were investigated in the present work. Nano‐size Mg‐Mn ferrite particles with diameter in the range of 8~ 15 nm were successfully formed via this method. The combustion temperature of the oxidation‐reduction was apparently occurred at 200°C. The result of X‐ray diffraction (XRD) analysis indicated that the as‐burnt powder affords a pure single spinel ferrite phase at low temperature. The thermal analysis of nitrate–citrate gels was characterized by DTA‐TG. The TEM and SEM observations give the morphology and microstructure of the products. The dielectric properties of the sintered Mg‐Mn ferrites were investigated by using HP/Agilent 4291B RF impedence/material analyzer. It was found that there was no maximum dielectric loss within the measured frequency range until 1 GHz due to excellent compositional control in this method.